2008
DOI: 10.1002/nur.20284
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress in survivors of suicide: Psychometric properties of the Perceived Stress Scale

Abstract: The purpose of this study was to evaluate the psychometric properties of three versions of the Perceived Stress Scale (PSS; American Sociological Association) in adults who had survived the death of a family member or significant other by suicide. Reliability and validity were examined. Exploratory factor analysis was conducted to assess dimensionality of the underlying constructs. All three versions of the PSS demonstrated acceptable reliability. Two shorter versions retained good psychometric properties and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
194
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(214 citation statements)
references
References 18 publications
17
194
0
3
Order By: Relevance
“…As análises fatoriais exploratórias, utilizando matriz de correlações policóricas, método de retenção do minimum rank factor analysis e o critério de retenção fatorial da análise paralela identifi caram uma estrutura unidimensional para a PSS-10, em concordância com estudos prévios (Campo-Arias et al, 2009;Cohen & Williamson, 1988;Luft et al, 2007;Mitchell et al, 2008). Este resultado era esperado, tendo em vista estudos prévios que demonstra-…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As análises fatoriais exploratórias, utilizando matriz de correlações policóricas, método de retenção do minimum rank factor analysis e o critério de retenção fatorial da análise paralela identifi caram uma estrutura unidimensional para a PSS-10, em concordância com estudos prévios (Campo-Arias et al, 2009;Cohen & Williamson, 1988;Luft et al, 2007;Mitchell et al, 2008). Este resultado era esperado, tendo em vista estudos prévios que demonstra-…”
Section: Discussionunclassified
“…Alguns estudos (Campo-Arias, Bustos-Leiton, & Romero--Chaparro, 2009;Cohen & Williamson, 1988;Luft, Sanches, Mazo, & Andrade, 2007;Mitchell, Crane, & Kim, 2008) encontraram, a partir de técnicas exploratórias e confi rmatórias, uma estrutura unifatorial para a escala, conforme postula a base teórica do instrumento (Cohen & Williamsom, 1988), enquanto outros encontraram uma estrutura bifatorial (Leung, Lam, & Chan, 2010;Roberti, Harrington, & Storch, 2010;Wongpakaran & Wongpakaran, 2010). Nestes casos, os fatores são interpretados como estresse (itens positivos) e coping/controle (itens negativos), apresentando níveis de correlações variando entre r = 0,51 e 0,65.…”
unclassified
“…" Mitchell, Crane, and Kim (2008) reported that the PSS-10 demonstrated good psychometric properties with adequate convergent and concurrent validity. The Cronbach's alpha of PSS-10 for the present study, measured at pre-intervention, post-intervention and three months later, ranged from 0.81-0.91.…”
Section: Self-compassion Scale-short Form Scs-sfmentioning
confidence: 99%
“…The 2-factor PSS-10 reduces 4 items it allows researchers collect data in a short period of time (Shacham, 1983). Although researchers have different arguments regarding dimensionality of PSS (Hewitt, Flett, & Mosher, 1992;Mitchell, Crane & Kim, 2008;Örücü, & Demir, 2009) it is for sure that 2-factor PSS-10 receive better support in sports contexts. The results are consistent with the earlier study by Hewitt and colleagues (Hewitt et al, 1992).…”
Section: Discussionmentioning
confidence: 99%